FILOSOFI DIBALIK METAFORA NOMINATIF WACANA DAN SURAT-SURAT POLITIK TAN MALAKA - Sawirman Sawirman (Universitas Andalas, 2012)
Tan Malaka’s political discourses involve various nominative metaphors as the reflection of pseudo lingual symbols, for instance: the strategic use of the word perdagangan ‘trade’ as the camouflage of the word perjuangan ‘struggle’, the use of the term firm and pabrik to avoid the term partai ‘party’, the use of the term rokok ‘cigarette’ which is meant as the rebellion, the hidden meaning behind the word choklat and cacao ‘chocolate’ was pemogokan ‘strike’, the signified behind the signifier kuda ‘horse’ was tentara ‘army’, and the word tebu ‘sugar cane’ indicates the concealed meaning of uang ‘money’. The nominative metaphors on those Tan Malaka’s political discouses and letters were analyzed by Sawirman-e135 frame.